The usable leftover one-dimensional cutting stock problem-a priority-in-use heuristic - Cherri, Adriana Cristina [UNESP]; Arenales, Marcos Nereu; Yanasse, Horacio Hideki (Wiley, 2013)
We consider a one-dimensional cutting stock problem in which the material not used in the cutting patterns, if large enough, is kept for use in the future. Moreover, it is assumed that leftovers should not remain in stock for a long time, hence, such leftovers have priority-in-use compared to standard objects (objects bought by the industry) in stock. A heuristic procedure is proposed for this problem, and its performance is analyzed by solving randomly generated dynamic instances where successive problems are solved in a time horizon. For each period, new demands arise and a new problem is solved on the basis of the information about the stock of the previous periods (remaining standard objects in the stock) and usable leftovers generated during those previous periods. The computational experiments show that the solutions presented by the proposed heuristic are better than the solutions obtained by other heuristics from the literature. © 2012 The Authors. International Transactions in Operational Research © 2012 International Federation of Operational Research Societies.
Keywords: Cutting stock problems; Usable leftovers; Computational experiment; Cutting patterns; Cutting stock; Cutting stock problem; Heuristic procedures; One-dimensional cutting stock problem; Time horizons; Usable leftover; Heuristic methods; One dimensional; Integer programming